(untitled) (Journal of Engineering and Health Sciences, 2019)
This study aims to identify the level of obesity awareness among nurses working in Alor Gajah District Health Clinic, Melaka. Quantitative studies with cross sectional methods were carried out. Random sampling is made by distributing questionnaires to respondents and the data wasrecorded and analyzed using the Statistical Package Social Science (SPSS) software. Descriptive analysis showed that all respondents are in high stages of obesity level. For the practice of exercise, the overall respondents (50.7%) were moderate to the lower level while 49.3% were at high levels. For healthy eating habits is at low level (65.8%) and (34.2%) high level. Inferential analysis showedthat there is a significant relationship between healthy eating habits and BMI through Chi square test. However, there isno significant relationship between knowledge and exercise practices with BMI respondents in this study. With regard to research findings, some suggestions have been raised as individuals who are overweight can lose weight if they live a healthy lifestyle by controlling their diet and increase physical activity such as daily exercise in recommended rates.